Protests, “acting-out”, group psychology, surplus enjoyment and neoliberal capitalism - Olivier, Bert (PINS-Psychology in Society, 2017)
How should one make sense of the recent student protests across South Africa, which seem to be motivated by grievances relating to various forms of financial exclusion, from registration and tuition fees to costs of accommodation, and later pre-election protests, triggered by competition among would-be party candidates? It appears that Freud and Lacan’s countervailing psychoanalytical concepts of “acting-out” and “transference” cast explanatory light on this variegated phenomenon – the former insofar as it is an index of repressed, unarticulated motives manifesting themselves in irrational behaviour resistant to “analysis”, instead of ethically accountable “acts”, and the latter, on the contrary, designating a process according to which subjects are receptive to, and act (or speak) according to the requirements of “successful analysis”, including the “subject supposed to know”. Cognisance must also be taken of the fact that the protestors constitute(d) groups, and that it should therefore be approached as such in psychoanalytical terms. Recourse to the Freudian notion of “group psychology” is heuristically helpful in this regard. This is augmented by focusing on what has, it is argued, functioned to trigger the protest behaviour, namely neoliberal capital, by way of considering Lacan’s account of capitalist discourse in Seminar 17 – together with its insightful interpretation by Juliet MacCannell – particularly the relation between surplus value and surplus enjoyment.